Explaining Military Change in China: Reintroducing Civilian Intervention. Issue 133 (2nd January 2022) - Dossi, Simone
ABSTRACT: Since the mid-1990s, the operational doctrine of the People's Liberation Army (PLA) has increasingly focused on jointness. For two decades, however, the PLA's organizational structure did not adapt accordingly. A major reform was eventually passed in 2015, with the establishment of a new joint operational command system. This 20-year institutional lag is explained by the changing pattern of civilian intervention in military affairs. Even more than doctrinal change, organizational change is likely to be met with resistance from within the military. A facilitating role is then played by civilians who provide external support to pro-reform senior military officers. Yet, such external support depends on the state of civil–military relations, which determines the room for civilian intervention in the military sphere.